Unravelling Methodologies for a Rational Lignin Valorisation Using Heterogeneously Catalysed Protocols - Luque, Rafael (Journal of Technology Innovations in Renewable Energy, 2015)
Lignin depolymerisation has recently a great deal of attention from scientists and companies worldwide due to the extensive possibilities of this recalcitrant material for the production of chemicals, fuels and materials. The natural complexity and stability of lignin bonds makes lignin depolymerization a highly challenging task. Several efforts have been directed towards a more profound understanding of the structure and composition of lignin in order to devise pathways and selectively cleave bridging bonds to break down the biopolymer into useful compounds. The present contribution aims to provide a series of key points in the field of lignin depolymerisation to provide an overview to the field for starting researchers.